OPTIMALISASI USAHA KESEHATAN SEKOLAH MELALUI PERILAKU HIDUP BERSIH DAN SEHAT DI SEKOLAH DASAR 10 TIMPEH - Hamidatul Yuni; Siti Nurhasanah; Nadia Chalida Nur; Yessy Markolinda; Trisfa Augia (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Elementary School 10 Timpeh is one of the schools in the 3T area in Sungai Bulian, Timpeh District, Dharmasraya Regency, with a distance of 197 km from Padang City. SDN 10 Timpeh has a School Health Unit (SHU) but has been inactive, and the room has been converted into a warehouse. This activity aims to reactivate and optimize SHU functions at SDN 10 Timpeh. The first method was carried out through training activities for ten students who were selected to become cadres of little doctors from classes 3,4, and 5. The second method was done with lectures, discussions about clean and healthy behaviour for all students. The strengthening of the theory is also accompanied by stimulation of the affective and psycho-motor domains of students through the exercise of using soap and running water, giving students fruit and milk, as well as the practice of handling students who move to school by a cadre of little doctors who have been previously selected. Evaluation of this program is done through pre-test and post-test. After training and coaching, there was a significant increase in students' knowledge of the little doctor's subject matter by 10 points, and the Wilcoxon test results showed an increase in student knowledge. The students of SDN 10 Timpeh were enthusiastic about this activity. The advocacy management results were strengthened by the issuance of a headmaster decree on the control of the SHU and the appointment of a supervisor of the SHU as well as an explanation of his job description. It is expected that the Public Health Centre, Schools, and coaches will continue to carry out these SHU activities on a scheduled and periodic evaluation.